2009
DOI: 10.1007/s10508-009-9482-x
|View full text |Cite
|
Sign up to set email alerts
|

Gazing Behavior During Mixed-Sex Interactions: Sex and Attractiveness Effects

Abstract: We investigated to what extent the length of people's gazes during conversations with opposite-sex persons is affected by the physical attractiveness of the partner. Single participants (N = 115) conversed for 5 min with confederates who were rated either as low or high on physical attractiveness. From a mating strategy perspective, we hypothesized that men's increased dating desire towards highly attractive confederates would lead to longer periods of gazing, whereas women's gazing would be less influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
2
13
1
Order By: Relevance
“…For instance, facial attractiveness was revealed to positively affect gaze behavior (e.g., longer gaze duration, larger cone of gaze etc.) in human beings (see e.g., Maner et al, 2003, 2007; Leder et al, 2010, 2016; van Straaten et al, 2010; Baranowski et al, 2016). Research in the field of social psychology revealed that attractive individuals are perceived as more socially capable, popular, and competent (Dion et al, 1972; Eagly et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, facial attractiveness was revealed to positively affect gaze behavior (e.g., longer gaze duration, larger cone of gaze etc.) in human beings (see e.g., Maner et al, 2003, 2007; Leder et al, 2010, 2016; van Straaten et al, 2010; Baranowski et al, 2016). Research in the field of social psychology revealed that attractive individuals are perceived as more socially capable, popular, and competent (Dion et al, 1972; Eagly et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively, facial attractiveness in male faces is not as important for women as is facial attractiveness in female faces for men. Although women showed attention bias toward HA male faces compared with LA male faces (Silva et al, 2016), the attentional bias toward HA oppositesex faces was significantly stronger for men than that for women (Kleck and Rubenstein, 1975;Fugita et al, 1977;van Straaten et al, 2010;Valuch et al, 2015;Mitrovic et al, 2018). Nevertheless, we should notice that the attractiveness in male faces may be different for women in different situations (e.g., in the ovulatory phase or not).…”
Section: Comparison Of the Cognitive Processing Of Facial Attractivenmentioning
confidence: 76%
“…Some studies have revealed that men may show a stronger attentional bias toward HA oppositesex faces than women may (Fugita et al, 1977;van Straaten et al, 2010;Valuch et al, 2015;Mitrovic et al, 2018). For example, evidence showed that heterosexual men spent less time fixating on LA faces than on HA opposite-sex faces, while there was no significant difference of fixation time between LA and HA faces among heterosexual women (van Straaten et al, 2010). Neurophysiological evidence also revealed that HA oppositesex faces elicited larger N170 and LPP than LA opposite-sex faces did for heterosexual men (Morgan and Kisley, 2014;Zhang et al, 2018).…”
Section: Cognitive Processing Of Facial Attractiveness In Adult Facesmentioning
confidence: 99%
See 1 more Smart Citation
“…Each camera recorded the face of the opposite person from a higher perspective than the eyes of the perceiver, herewith providing a clear image of gazing directions. The setting of the experiment has been successfully used before in a study measuring social interaction behavior and gazing in opposite sex-dyads (Van Straaten, Holland, Finkenauer, Hollenstein, & Engels, 2010). When seated, the participants were given a short instruction to talk about nightlife in the city for five minutes (Task 1).…”
Section: Methodsmentioning
confidence: 99%